Synergistic Anti-Cancer Effects of Curcumin and Thymoquinone Against Melanoma - Hana Mohd; Bozena Michniak-Kohn (Antioxidants)
Combining anti-cancer agents in cancer therapies is becoming increasingly common because of their improved efficacy, reduced toxicity, and decreased risk of resistance development. Melanoma, a highly aggressive form of skin cancer characterized by limited treatment options due to chemoresistance, poses a considerable challenge for effective management. Here, we test the hypothesis that dietary supplements such as thymoquinone (TQ) and curcumin (CU) cooperatively modulate cancer-associated cellular mechanisms to inhibit melanoma progression. Through a series of in vitro experiments utilizing the A375 melanoma cell line, including assessments of cell viability, apoptosis, multicellular tumor spheroid models, reactive oxygen species (ROS) quantification, metabolomics analysis, and RNA sequencing, we established that the combined application of TQ and CU exhibited superior anti-tumor effects compared to their individual use. Our results indicate that the combination treatment significantly inhibited cell viability and induced apoptosis more effectively than either agent alone, with optimal synergy observed at concentrations of 25 µM CU and 10 µM TQ against A375 cells. Additionally, the combination treatment markedly elevated ROS levels, selectively activating the mitochondrial apoptotic pathway via caspase-9. Differential gene expression analysis further revealed a unique synergistic effect of the combination treatment, with enhanced regulation of genes related to oxidative stress and apoptosis. Notably, pathways such as mitochondrial apoptotic signaling and redox homeostasis were more effectively influenced by the combination, with genes such as GPX3, CYP4F11, and HSPB8 cooperatively regulated. Overall, the findings suggest that, in combination, TQ and CU acts synergistically against melanoma; however, further experimental and clinical studies are required to confirm its therapeutic potential.